Supremasi Sipil Atas Militer Pasca-2024: Membaca Resistensi Institusional dalam Politik Hukum Indonesia - Della, Ismarini Della Purnama; Novaranty Zura Dwiputri; Irwan Triadi (Universitas Muhammadiyah Kotabumi, 2025)
This research focuses on the civil-military supremacy principle within the context of Indonesia’s constitutional democracy, specifically post-2024 political and legal developments. The study examines how the relationship between civilian authorities and the military has evolved, highlighting the institutional resistance within the Indonesian military that challenges civil supremacy. The chosen topic is vital due to the increasing influence of the military in civilian affairs, notably in the political and administrative sectors. Utilizing a normative juridical-critical methodology, this research analyzes primary legal texts, such as the 1945 Constitution, the Indonesian National Army Law (UU TNI), and the Military Court Law, alongside recent amendments. It explores the inconsistency between Indonesia's formal civil supremacy principles and the military’s continued privileges, which hinder the full implementation of democratic governance. The research also highlights the growing political and institutional dynamics, including the controversial expansion of military roles post-2024 and its implications on national security and civilian control. The findings suggest that institutional military resistance to civil supremacy has resulted in legal dualism, undermining the rule of law and democratic consolidation. The study contributes to understanding the challenges of strengthening civilian authority in Indonesia's governance and offers recommendations for legal reforms, including the integration of military and civilian judicial systems, increased civil society oversight, and sustainable policymaking. Ultimately, this research underscores the critical need to preserve civilian supremacy to protect Indonesia's constitutional democracy